Creating a Caring Education Institution: From a Sinking to a Moving Secondary School - Ngwako Solomon Modiba (E-Journal of Humanities, Arts and Social Sciences)
This paper assesses what it takes to emerge with caring and moving education institution from the initially sinking one whose scholarly results were deplorably low from the perspectives of teachers serving in the School Governing Body (SGB) and the Representative Council of Learners (RCL). This paper was motivated by diverse discourses about scholarly performances, most of which are mainly based on the perspective of external education stakeholders other than teachers and learners serving in a secondary school’s governing body. The paper is conceptual and empirical in nature within the qualitative research paradigm. The question guiding this paper is: how long does it take a sinking secondary school to be turned around into a caring and moving secondary school? Narrative enquiry and interviewing techniques were employed to generate data. Out of the population of sixteen secondary schools in one of the circuits in the Waterberg district in Limpopo Province, South Africa, six were conveniently sampled for study. In each of the six sampled secondary schools, only representatives of the teacher components in the School Governing Body and chairpersons of the Representative Council of Learners (RCL) became research participants. Findings revealed that firstly, caring and moving schools build trust with stakeholders. Secondly, caring and moving schools experience minimal derelict teaching duties by educators. Thirdly, caring and moving schools witness less derelict learning responsibility by scholars. Fourthly, there is subjugation of the culture of laziness in caring and moving secondary schools. Fifthly, a policy of remedial lessons for struggling scholars, is upheld in caring and moving schools. Lastly, caring and moving schools experience less gaping leadership voids in their ranks. The researcher recommends that sinking secondary schools share a warm disposition and be friendly with everyone to successfully become caring and moving secondary schools. This paper is likely to add to the existing body of literature as regards what constitutes a sinking and moving education institution and the causative factors behind each of them.